GRK6 Depletion Induces HIF Activity in Lung Adenocarcinoma - Yao, Sumei; Ertay, Ayse; Zhou, Yilu; Yao, Liudi; Hill, Charlotte; Chen, Jinliang; Guan, Yangbo; Sun, Hui; Ewing, Rob M.; Liu, Yifei; Lv, Xuedong; Wang, Yihua (Frontiers in Oncology, 2021)
G protein-coupled receptor kinase 6 (GRK6) is expressed in various tissues and is involved in the development of several diseases including lung cancer. We previously reported that GRK6 is down-regulated in lung adenocarcinoma patients, which induces cell invasion and metastasis. However, further understanding of the role of GRK6 in lung adenocarcinoma is required. Here we explored the functional consequence of GRK6 inhibition in lung epithelial cells. Analysis of TCGA data was coupled with RNA sequencing (RNA-seq) in alveolar epithelial type II (ATII) cells following depletion of GRK6 with RNA interference (RNAi). Findings were validated in ATII cells followed by tissue microarray analysis. Pathway analysis suggested that one of the Hallmark pathways enriched upon GRK6 inhibition is ‘Hallmark_Hypoxia’ (FDR = 0.014). We demonstrated that GRK6 depletion induces HIF1α (hypoxia-inducible factor 1 alpha) levels and activity in ATII cells. The findings were further confirmed in lung adenocarcinoma samples, in which GRK6 expression levels negatively and positively correlate with HIF1α expression (P = 0.015) and VHL expression (P < 0.0001), respectively. Mechanistically, we showed the impact of GRK6 on HIF activity could be achieved via regulation of VHL levels. Taken together, targeting the HIF pathway may provide new strategies for therapy in GRK6-depleted lung adenocarcinoma patients.